An International Survey of Research in Language Testing 1977-79 / Randall L. Jones. - Jones, Randall L. (Distributed by ERIC Clearinghouse, 1980)
This compilation lists 286 current second language testing research projects in the United States and abroad. Each listing provides the name of the principal investigator, address, title of project, areas covered by the research, and a 50- to 100-word descriptive statement of the project. Date of completion or projected completion of each project is indicated. The directory is indexed by language and by research area. (JB)